PENGARUH PEMBIAYAAN PRODUK KUR SYARIAH TERHADAP PERKEMBANGAN UMKM KOTA PROBOLINGGO - fajri, Ahmad; Fama, Eugene (universitas Islam Zainul Hasan Genggong, 2024)
This research aims to determine the influence of KUR Syariah product financing on the development of MSMEs. The population in this study were MSMEs who were registered as customers and used financing funds. By distributing questionnaires or questionnaires to customers at the CPS Probolinggo Sharia pawn shop, there were 70 respondents. The sample from this research used random sampling and obtained a sample of 41 respondents. For data analysis, we used the SPSS version 29 program. The results of the research showed that KUR Syariah product financing had a positive effect on the development of MSMEs at the CPS Probolinggo Sharia pawnshop. Customer business development has increased both in terms of business capital, increased turnover and increased income.